Exploring the dynamics of African swine fever transmission cycles at a wildlife-livestock interface. (April 2023) - Mugabi, Francis; Duffy, Kevin J.
Abstract: African swine fever (ASF), a contagious disease of pigs, can be economically devastating. At a wildlife–livestock interface, depending on the presence and interactions of domestic pigs, wild pigs, and soft ticks, three transmission cycles have been proposed for the persistence of ASF: a wild pig-domestic pig-tick cycle, a domestic pig-tick cycle, and a domestic pig cycle, but to date, their relative importance on the outbreak and persistence of the disease is not clear. A stochastic model that considers these cycles is formulated and analysed to assess their impacts on the outbreak and persistence of the disease. Using a multitype branching process approximation, it is shown that all cycles can result in very large probabilities of disease outbreaks. Numerical results show that the disease can be endemic if the ticks are not controlled. If ticks are controlled, disease extinction is certain, regardless of the cycle, but the time to extinction can be long. These findings have important implications for the prevention and control of ASF outbreaks at a wildlife–livestock interface.